Comparisons of College Students’ Enjoyment in Physical Activity & Exergames - Oh, Yoonsin; Wiggins, Matthew S.; Leibham, Mary Beth (European Scientific Journal, ESJ, 2016)
The purpose of this study was to compare college students’ enjoyment levels in three domains of activity (traditional physical activities, exergames, and non-exergames). Volunteers (n = 141) from a Midwestern university completed an online survey composed of a modified version of the Physical Activity Enjoyment Scale (PACES). Significant differences were detected across the three domains regarding level of enjoyment, F(2, 232) = 32.49, p < .001, with the highest enjoyment levels reported in the traditional physical activity domain. Additional results revealed that Wii Sports (49%) and Just Dance (29%) had the highest percentage of use with exergamers, while non-exergame participants reported playing video games such as Pokémon, Zelda, Mario Kart, Madden (59%), and Clash of Clans (25%). These results suggest that traditional physical activities and exergaming activities are psychologically enjoyable pursuits for college-aged individuals that can help increase their physical health and quality of life.